Effect of the coexposure of sulfadiazine, ciprofloxacin and zinc on the fate of antibiotic resistance genes, bacterial communities and functions in three-dimensional biofilm-electrode reactors. (January 2020) - Li, Hua; Song, Hai-Liang; Xu, Han; Lu, Yi; Zhang, Shuai; Yang, Yu-Li; Yang, Xiao-Li; Lu, Yu-Xiang
Graphical abstract: Highlights: Coexposure of Zn increased the ARG abundance in 3D-BER. Electrical stimulation enhanced pollutants removal but increased their accumulation. Electrical stimulation enriched ARGs on electrodes but reduced them in the effluent. The coexposure process significantly affected the bacterial community functions. The shift in hosts to substrates reduced the abundance of ARGs in the effluent. Abstract: Three-dimensional biofilm electrode reactors (3D-BERs) with high treatment efficiency were constructed to treat wastewater containing sulfadiazine (SDZ) and ciprofloxacin (CIP) coexposure with Zinc (Zn). The results showed that coexposure to target antibiotics and Zn increased the absolute and relative abundances of target antibiotic resistance genes (ARGs). Additionally, the target ARG abundances were higher on cathode of 3D-BER compared with ordinary anaerobic reactor while the abundances of total ARGs were decreased in the effluent. Meanwhile, redundancy analysis results revealed that the composition of bacteria carrying ARGs was greatly influenced in the cathode by the accumulation of Zn and antibiotic, which dominated the changes of ARG abundances. Additionally, ARGs with their host bacteria revealed by network analysis were partially deposited on electrode substrates when being removed from wastewater. Thus, 3D-BER exhibits capability of simultaneously eliminating antibiotic and Zn, and greatly reduces the risks of ARGs spread.